Colon cancer screening with CT colonography: logistics, cost-effectiveness, efficiency and progress - Obaro, Anu E (Br J Radiol, 2018)
Colorectal cancer (CRC) incidence and mortality can be significantly reduced by population screening. Several different screening methods are currently in use, and this review focuses specifically on the imaging technique computed tomographic colonography (CTC). The challenges and logistics of CTC screening, as well as the importance of test accuracy, uptake, quality assurance and cost-effectiveness will be discussed. With comparable advanced adenoma detection rates to colonoscopy (the most commonly used whole-colon investigation), CTC is a less-invasive alternative, requiring less laxative, and with the potential benefit that it permits assessment of extra colonic structures. Three large-scale European trials have contributed valuable evidence supporting the use of CTC in population screening, and highlight the importance of selecting appropriate clinical management pathways based on initial CTC findings. Future research into CTC-screening will likely focus on radiologist training and CTC quality assurance, with identification of evidence-based key performance indicators that are associated with clinically-relevant outcomes such as the incidence of post-test interval cancers (CRC occurring after a presumed negative CTC). In comparison to other CRC screening techniques, CTC offers a safe and accurate option that is particularly useful when colonoscopy is contraindicated. Forthcoming cost-effectiveness analyses which evaluate referral thresholds, the impact of extra-colonic findings and real-world uptake will provide useful information regarding the feasibility of future CTC population screening.